Quality of Life in Patients with Chronic Heart Failure, After Cardiac Resynchronization Therapy - Khaydarov Sanjar Nizamitdinovich; Khusainova Munira Alisherovna (Zien Journals, 2022)
To assess changes in quality of life (QOL) in patients with chronic heart failure (CHF), who received cardiac resynchronisation therapy (CRT) one year after surgery. Materials and methods. The study enrolled 82 patients (68 men and 14 women) aged 30 to 74 years (mean age 55.8±9.2 years) who underwent biventricular pacemaker implantation for SRT. Depending on the EchoCG response to SRT, patients were divided into two groups: 56 people with positive response (responders) and 26 persons with insufficient response (nonresponders). The SF-36 questionnaire was used to assess patients' QOL. The results Questionnaire results were presented as scores on 8 scales: "physical functioning (PF)", "physical role functioning (RP)", "pain scale (BP)", "general health status (GH)", "vitality scale (VT)", "social functioning scale (SF)", "emotional role functioning (RE)", "psychological health (MH)". Vital signs were assessed before SRT and again one year after surgery. Results. One year after HRT treatment, a statistically significant increase of QOL index was observed in patients with CHF PF (before SRT 46.3±26.2, after SRT 53.1±27.7, p=0.023). There was a tendency to increase of Vital signs: VT (before SRT 47.1±20.1, after SRT 51.8±20.1, p=0.081), SF (before SRT 61.58±25.06, after SRT 67.07±24.57, p=0.088). In the respondent group one year after SRT, there was a statistically significant increase in CSH: PF (from 45.2±26.0 to SRT 57.1±26.4, p=0.001), VT (from 46.5±20.8 to 54.4±19.7, p=0.010), SF (from 60.9±26.4 to SRT 70.8±20.8, p=0.012). There was a tendency for an increase in the CV indices: BP (from 57.5±25.1 to 64.8±23.8, p=0.079), GH (from 45.3±16.4 to 49.1±18.0, p=0.079), MH (from 57.7±18.9 to 62.5±17.7, p=0.081). In the nonsponder group, there was a decreasing trend in the RE (from 46.2±45.3 to 26.9±41.1 p=0.069).
Keywords: quality; chronic heart failure; cardiac resynchronisation therapy